Timber-framed Houses Built for the Court Members after the 1894 Earthquake in Istanbul: Rationalization of Construction Techniques. Issue 5 (3rd July 2016) - Acar, Damla; Mazlum, Deniz
ABSTRACT: During the second half of the 19th century, Western European industrial achievements affected construction techniques in Istanbul. Ottoman archival documents reveal the usage of industrial materials and machine shaped timber elements, which brought the rationalization of traditional timber construction techniques. After the 1894 Istanbul earthquake, many post-earthquake timber-framed houses constructed as temporary shelters in the precincts of masonry mansions were rapidly built due to the rationalization in building techniques. Since there is not any inventory for the industrial materials and techniques used in the second half of the 19th century in Istanbul, their determination is of crucial importance in the process of conservation.